Attractiveness of the complex tourist offer of monasteries and villages of Fruška gora from the aspect of potential tourists - Škrbić Iva; Milošević S. (University Educons, Faculty of Sports and Tourism, Novi Sad, 2012)
If the revival of Fruška gora villages is to be achieved and their extinction prevented, economic activity must be revived, thus enabling the existential conditions for country life. One of the alternatives is to revive the tourist village through the creation of high-quality tourism products and/or services that could be realized on the market. Merging of Fruška gora villages and monasteries may be provided with the necessary resources. However, before planning the tourist products and services, it is necessary to examine the target market demand and determine if there is potential for travel demand. If so, it would generate realistic demand after a market activation of tourism products and services. Therefore, the subject of this paper is rating of attitudes and opinions of the residents of the city of Novi Sad of the particular forms of tourism products / services that might be a part of the offer of the Fruška gora monasteries and villages in order to prove or disprove the validity of the programming of tourist products and services in Fruška gora villages and monasteries, as well as their placement on the tourist market. The study included 75 adult respondents who live in the city of Novi Sad. Survey was used, and data were analyzed by statistical analysis. The results showed that the residents of Novi Sad recognize monasteries and villages of Fruška gora as a valuable resource. There is a high level of interest in this type of tourist products and services that can result in a satisfactory real travel demand.